2012
DOI: 10.1016/j.phytochem.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in free and bound fractions of aroma compounds of four Vitis vinifera cultivars at the last ripening stages

Abstract: The volatile composition of white Agudelo, Blancolexitimo, Godello and red Serradelo cultivars (NW Spain) harvested at two different stages of ripening have been evaluated. C(6)-compounds, alcohols, volatile fatty acids, monoterpenes, C(13)-norisoprenoids, volatile phenols and carbonyl compounds were identified and quantified in free and glycosidically bound forms by gas chromatography-mass spectrometry (GC-MS). The total volatile concentration showed a significant increase between the two ripening stages stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 54 publications
7
45
0
2
Order By: Relevance
“…At all locations, the total amount of aroma precursors increased during ripening. This is consistent with previous studies on different Vitis vinifera grape varieties (Fenoll et al, 2009;Vilanova et al, 2012). This behaviour is common because most active aroma compounds are lipophilic; however, high, localised concentrations of lipophilic molecules can be toxic to the plant by disrupting cellular membranes, or can induce cell death (Sikkema et al, 1995;Hjelmeland & Ebeler, 2015).…”
Section: Glycosidically Bound Volatile Compoundssupporting
confidence: 91%
“…At all locations, the total amount of aroma precursors increased during ripening. This is consistent with previous studies on different Vitis vinifera grape varieties (Fenoll et al, 2009;Vilanova et al, 2012). This behaviour is common because most active aroma compounds are lipophilic; however, high, localised concentrations of lipophilic molecules can be toxic to the plant by disrupting cellular membranes, or can induce cell death (Sikkema et al, 1995;Hjelmeland & Ebeler, 2015).…”
Section: Glycosidically Bound Volatile Compoundssupporting
confidence: 91%
“…Free linalool reached its maximum on September 13 (technological maturity or stage E-L 38) and decreased during over-ripening. A similar behavior was observed in 2005 and 2007, even though the peak corresponded to slightly earlier stages (Figure 1E), proving that technological and aroma ripening might not occur at the same time (Vilanova et al, 2012). Otherwise, free geraniol and nerol as well as the three bound forms showed a steady increase in their content during the sampling period.…”
Section: Resultssupporting
confidence: 76%
“…These include free volatile metabolites such as alcohols, aldehydes, and methoxypyrazines, and low concentrations of esters, terpenes, and norisoprenoids, as well as nonvolatile glycosylated aroma precursors that can impart fruity, floral, spicy, or vegetative characters to wines (Lopez et al 2004, Sánchez-Palomo et al 2005, Canuti et al 2009, del Caro et al 2012, Dennis et al 2012, Flamini et al 2014, Hampel et al 2014. Vilanova et al (2012) found that in some Spanish cultivars, the accumulation of volatiles and precursors was not proportional to the increase in sugar concentration, showing that sugar ripeness does not necessarily equal flavor ripeness. Anthocyanins, flavonols, and tannins also accumulate during ripening, influencing the color, taste, and mouthfeel of wines, but there is evidence suggesting that anthocyanin and flavonol concentrations may decline late in berry development , Kennedy 2008, Bindon et al 2013, 2014b.…”
mentioning
confidence: 99%